Emergent, distributed, and orchestrated: Understanding leadership through frame analysis. (October 2019) - Alvehus, Johan
Leadership scholars are beginning to understand leadership as a distributed phenomenon, produced in interaction and emerging in social situations. Although this perspective has contributed to understanding leadership processes in more detail, it has also been noted that its proponents have largely neglected power and asymmetrical hierarchical relations. In this paper, I address these issues by drawing on Erving Goffman's notion of frame analysis. Through detailed analysis of the interactions in a core-values session, I show how leadership processes that appear to be distributed and emergent from the participants' framework appear orchestrated when understood from the manager's framework. The analysis reveals how power asymmetries operate in the framing of the situation, and how the experience of leadership differs among participants. Talk, text, tools, and movements in time and space all contribute to establish frameworks, and differences in access to these modalities show power asymmetries. The paper highlights how the experience of leadership is framed and how power asymmetries constitute this framing. It thereby contributes to multimodal, constructivist theories of distributed leadership by showing how leadership is simultaneously emergent, distributed, and orchestrated.